Operations research : An introduction - Taha, Hamdy A. (Chennai: Pearson Education, 2007)
This eighth edition of Operations Research continues to build on the strengths of the first seven editions, providing balanced coverage of the theory, applications, and computations of operations research. This is a major revision, one that streamlines the presentation of the text with emphasis on the applications and computations in operations research. Complex mathematical concepts are effectively explained by means of carefully designed numerical examples, essentially eliminating the need for formal mathematical proofs. The integration of practical applications of software allows students to test concepts that could not, otherwise, be presented effectively. The book includes fully analyzed practical situations and each chapter concludes with summary applications borrowed from published case studies.
Includes bibliographical references.; Appendices A-C, 660-722p.; Index 723-733p.
Keywords: Operational Research